Analysis of Recurrence Risk After Radical Surgery for Differentiated Thyroid Carcinoma Based on Fibroblast Growth Factor Receptor 4 and Inflammatory Cytokines: FGFR4 diagnosis of differentiated thyroid cancer - Sha, Yingying; Hu, Yongjie; Huang, Peifei (Journal of Medical Biochemistry, 2025)
Objective: This study aimed to evaluate the synergistic role of fibroblast growth factor receptor 4 (FGFR4) and inflammatory cytokines (interleukin-6 [IL-6], tumor necrosis factor-α [TNF-α], and C-reactive protein [CRP]) in predicting recurrence of differentiated thyroid carcinoma (DTC) after radical surgery, and to develop a combined predictive model for improved postoperative risk stratification.Methods: We enrolled 102 DTC patients treated between February 2022 and January 2024, along with 98 healthy controls. Serum levels of FGFR4, IL-6, TNF-α, and CRP were measured preoperatively and postoperatively using ELISA. Independent risk factors were identified through logistic regression, diagnostic performance was assessed using ROC analysis, and correlations of FGFR4 and inflammatory cytokines with postoperative recurrence were evaluated.Results: Preoperative levels of FGFR4, IL-6, TNF-α, and CRP were significantly elevated in DTC patients compared to healthy controls (P